TINGKAT PENGETAHUAN AKSEPTOR KB SUNTIK 3 BULAN TENTANG AMENORE SEKUNDER AKIBAT PEMAKAIAN KB SUNTIK 3 BULAN DI PUSKESMAS MUMBULSARI - Uswatun Hasanah; Moh. Wildan; Musia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2016)
Given the injectable contraceptive method is one effective way of family planning, and the more the number of selected users, but still many are also obtained syringes acceptor kontrasepasi samping.Tujuan effects experienced researchers to determine the level of knowledge of family planning acceptors injecting 3 months of amenorrhea side effects in the village of Taman Sari Subdistrict Mumbulsari in good level, pretty and less. The research used a descriptive quantitative research. The sampling technique used in this study is sampling saturated. The tools used for data collection was a questionnaire. According Nursalam (2003), the results to determine the level of knowledge acquisition are categorized according to the following data: Good: 76-100%, Enough: 56-75%, Poor: <56%. Based on the level of knowledge of family planning acceptors injecting 3 months in the village of Taman Sari subdistrict Mumbulsari 2014 namely, (Both 18.18%), (Simply 36.36%), (less 45.45%). Mother's knowledge about the side effects of amenorrhea can affect acceptor in using injectables 3 months, the knowledge can be influenced by age and education. Mother's education level affects the acceptor knowledge about the side effects injectables ie 3 months of amenorrhea. Based on the conclusions of this Scientific Writing in response to the research objectives is the level of knowledge of family planning acceptors injecting 3 months in the village of Taman Sari subdistrict Mumbulsari 2014 namely, Well 18.18%, 36.36% Enough, Less 45.45%. This is influenced by the majority of respondents elementary education and not school.